In Vitro Characteristics of a Combination of Thymoquinone-Resveratrol Loaded and Targeted Nanodrug Delivery System - Khattabi, Areen; Alqdeimat, Diala; Sabbar, Eilaf; Talib, Wamidh (Jordan Journal of Pharmaceutical Sciences, 2020)
The objective here is to study the in vitro characteristics of a combination of anticancer agents made of Thymoquinone and Resveratrol (TQ-RES), when loaded into our previously prepared targeted nanodrug delivery system (TNDDS). Our system based on silica nanoparticles (NPs) and modified with a long polymer, Carboxymethyl-β-Cyclodextrin (CM-β-CD) and folic acid (FA), respectively. The Encapsulation Efficiency (EE) and the release rate were measured using UV Spectrophotometer. The loading capacity (LC) was calculated using a specific equation and Thermal Gravimetric Analysis (TGA). The cell toxicity and apoptosis induction were measured using MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide) assay and by determining the Caspase-3 Activity, respectively. The (EE) and the (LC) were high (88% and more than 2%, respectively). The release rate of (TQ-RES) from targeted NPs was slower than the free drugs within the first few hours, but became similar after 24 hours. The percentages of cell toxicity were also similar for these samples. However, they were higher compared to loaded-nontargeted NPs and unloaded-targeted NPs. The same trend was noticed for the percentages of cell apoptosis. Attaining the benefits of this TNDDS will open the door for further in vivo investigations and hence its use for targeted treatment of cancer.